“One fits all?”: Resilienz als vielseitiges Konzept in der Raum- und Umweltentwicklung - Schiappacasse, Paulina; Müller, Bernhard (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
Resilience ranks high on the environmentally oriented research agenda on sustainable urban and regional development. The annual “Global Forum on Urban Resilience and Adaptation” has become a meeting point for academia and practice. The United Nations 2030 Agenda for Sustainable Development uses the term in two of their 17 Sustainable Development Goals, i.e., in Goal No. 9 on infrastructure as a basis for economic development and No. 11 on cities and human settlements. Moreover, resilience has become a prominent topic in the New Urban Agenda. Against this background, the article provides an overview of recent discussion on resilience. It scrutinizes how the concept has been used by different researchers from diverse disciplines with special reference to urban, regional and environmental studies. A systematic literature review on resilience was carried out in order to shed light on recent developments of thought and practice. All in all, 650 articles were reviewed. Following an introduction into the topic and description of the applied methodological approach, different facets of the debate on resilience are presented, and conclusions are drawn. It can be seen that the discussion of resilience needs more specificity, transdisciplinary approaches, and regional contextualization, especially in urban and regional development studies in the countries of the global south.
Keywords: Resilience; Literature review; Regional development; Sustainable development goals